Effectiveness of Music Therapy Intervention on Pain Levels in Patients with Primary Brain Tumor - Nurfallah, Idha; Kariasa, I Made (Jurnal Kesehatan - STIKes Prima Nusantara, 2023)
Introduction: Headache is a symptom that always occurs in brain tumours. During the disease, the patient experiences moderate to severe pain. Headaches gradually become more frequent and severe, as do nausea and vomiting, memory disturbances, seizures, balance disturbances and the risk of death—effective pain management in tumours whose treatment requires pharmacological and non-pharmacological interventions. Music therapy is part of complementary therapy. Music therapy has advantages as an intervention that can be applied in a simple, non-invasive, non-pharmacological relaxation stimulant that is safe, inexpensive, and effective.Objective: This review aims to explore and synthesize the scientific literature on music therapy as a non-pharmacological intervention to manage pain in primary Brain Tumor patients.Methods: The articles were searched in the SpringerLink, Proquest, Google Scholar, and Scopus databases using keywords and boolean operators. Searches used AND, OR, and NOT to produce targeted search results. Inclusion criteria for pain in brain tumors, full text, published within the last ten years from 2012 to 2022, provide information on non-pharmacological strategies in managing pain in primary brain tumors and are written in English. From a total of 8238 journals found, 12 were selected.Results: Based on a review of 12 selected journals, it was found that non-pharmacological management of music therapy effectively reduced pain in brain tumors.In conclusion, music therapy interventions effectively and safely reduce pain and increase patient comfort. Music therapy is a cheap, simple, non-invasive, and non-pharmacological method with no side effects; it can be used as an adjunct for analgesics and relaxation—the effectiveness of music therapy in reducing the pain of tumor or cancer patients.